Motif dan kekerapan penggunaan Facebook dalam kalangan pelajar universiti - Mahmud, Mohd Zaidi; Omar, Bahiyah (Penerbit UKM, 2013)
Facebook is the most popular social network sites in Malaysia. The popularity of this site was well-liked among youth as well as university students. This research aims to study the motives and the frequency of university students on the usage of Facebook. A survey involving 400 Universiti Sains Malaysia students was conducted and was analysed quantitatively. The statistical analysis of Factor Analysis has yielded five motives – coolness and companionship, to entertain, relationship maintenance, virtual community, and information seeking - for using Facebook. This research also examined the relationship of the five motives with the frequency of using Facebook through the total number of friends and total hour spent on Facebook in a week. The result demonstrated that three motives – coolness and companionship, t o e n t e r t a i n and information seeking – were significantly related to the frequency of using Facebook. However, to entertain has a significant motive which dominantly supports the regression model in this research.